2008
DOI: 10.1002/jssc.200800189
|View full text |Cite
|
Sign up to set email alerts
|

Methacrylate‐based short monolithic columns: Enabling tools for rapid and efficient analyses of biomolecules and nanoparticles

Abstract: This review describes the novel chromatography stationary phase--a porous monolithic methacrylate-based polymer--in terms of the design of the columns and some of the features that make these columns attractive for the purification of large biomolecules. We first start with a brief summary of the characteristics of these large molecules (more precisely large proteins like immunoglobulins G and M, plasmid deoxyribonucleic acid (DNA), and viral particles), and a list of some of the problems that were encountered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 56 publications
0
39
0
Order By: Relevance
“…But further research with use of measurements of the serotype-specific neutralizing antibodies to adenovirus or isolation/identification of specific adenovirus like particles in serum and adipose tissue samples using convective interaction media (CIM) monolithic column technology [50] in this group of OW/OB females should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…But further research with use of measurements of the serotype-specific neutralizing antibodies to adenovirus or isolation/identification of specific adenovirus like particles in serum and adipose tissue samples using convective interaction media (CIM) monolithic column technology [50] in this group of OW/OB females should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Another main advantage of monoliths is their flow-independent DBC allowing straight-forward scalability [3,[26][27][28]. A direct comparison between monoliths and particle-based resins for the purification of virus-like particles from yeast homogenate has been conducted by Burden et al The authors concluded that the monoliths are three-fold superior in terms of DBC with equivalent recovery in yield (90%) compared to particle-based resins [29].…”
Section: Adsorption Area and Dynamic Binding Capacitymentioning
confidence: 99%
“…Monolithic supports are easy to scale up without the need for column modifications [3,26]. Monolithic disks can be stacked up to four disks in the same housing, increasing efficiency and capacity without compromising resolution [3].…”
Section: Scalabilitymentioning
confidence: 99%
“…Monolith is a name for the chromatographic stationary phase consisting of a single piece of highly porous material (Barut et al, 2008). They are prepared in various dimensions with agglomeration-type or fibrous microstructures.…”
Section: Monolithic Supportsmentioning
confidence: 99%